Synthesis, Cytotoxicity, Antibacterial and Antioxidant Activity of New 2-Substituted Benzimidazole Containing 1,2,4-Triazoles - Aryal, Prateek; Shakya, Bhushan (Journal of Nepal Chemical Society, 2023)
The development of a potent new drug with high biological activity is a challenge in drug design and is of strategic importance. Due to the increasing resistance of pathogens on the available drugs, there is always a demand for designing a potent drug with high biological activity. The pharmacological effects have been observed in compounds containing different moieties of pharmaceutical importance such as triazole, Schiff’s base, benzimidazole.Triazole thione, Schiff’s bases, and two new compounds containing three pharmacophores viz. triazole, benzimidazole, and Schiff base incorporated in a single compound were prepared by applying different synthetic reactions. Different spectroscopic methods, including FT-IR, UV-vis, 1H-NMR, and 13C-NMR, were used to confirm the structure of the prepared compounds. All compounds exhibited moderate antibacterial activity against Staphylococcus aureus (ATCC 6538P) and Staphylococcus epidermidis (ATCC 1228). Antioxidant activity was carried out by DPPH radical scavenging test and among the tested five compounds, the IC50 value of 4-amino-3-(2-hydroxyphenyl)-1H-1,2,4-triazole-5(4H)-thione was found to be 32.364 μg.mL-1 which is closer to the ascorbic acid that was found to be 28.546 μgmL-1. All tested compounds were toxic against brine shrimp where 2-(5-((1H-benzo[d]imidazol-2-yl)thio)-4-((4-chlorobenzylidene) amino)-4H-1,2,4-triazol-3-yl) was comparatively more toxic (LC50= 26.827 μgmL-1).